Iconographic simultaneity in baroque sculpture: Antonio del Castillo and the erroneous authorship of Benamejí’s Jesus Nazareno - Ramírez González, Sergio (Eikón / Imago, 2022)
The present work intends to approach the iconographic universe of the order of the discalced carmelites, through two sponsored models by the holy reformers, specifically Christ tied to the column and Jesus Nazareno passionist representations. These two works had an enormous spread in their own convents after being part of the mystical experiences of Teresa of Avila and saint John of the Cross. Such fundamentals, together with contribution of new unedited documentation, will serve as starting point to elucidate the confusion and ascription errors on Benamejí (Córdoba) church’s Jesus Nazareno. These last years it has been linked to the good work of the Antequera-born sculptor Antonio del Castillo. It is now discovered through that this work is not the same as the one he made in 1695 to be shown at the today’s lost carmelite convent Our Lady of the Remedies. It sort of equates to Christ tied to the column, found at the same church, who was in another time called Jesus of the Remedies, and who alternately showed both iconographies, as he acted with the trappings and elements of the Passion.